2021
DOI: 10.2144/fsoa-2020-0200
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Recurrent vaccine-triggered Gianotti–Crosti Syndrome

Abstract: Gianotti–Crosti syndrome (GCS) is a self-limited benign dermatosis, clinically characterized by a monomorphic papular or papulovesicular eruption symmetrically distributed on the limbs and face of children. Various viral and vaccine triggers have been associated with GCS. Recurrences are uncommon but have been reported. We report a case of recurrent vaccine-triggered GCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 17 publications
1
14
0
15
Order By: Relevance
“…Assaf et al reported a recurrence case following 2 different types of vaccination: vaccinated with hepatitis B and 3 months later having recurrence after receiving MMR vaccine. 5 On the other hand, two cases were reports that administration of a single episode MMR vaccine does not associate with GCS cases recurrence. 5,9 Education to the parents about GCS is important to prevent unnecessary tests and treatment also vaccination avoidance later.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Assaf et al reported a recurrence case following 2 different types of vaccination: vaccinated with hepatitis B and 3 months later having recurrence after receiving MMR vaccine. 5 On the other hand, two cases were reports that administration of a single episode MMR vaccine does not associate with GCS cases recurrence. 5,9 Education to the parents about GCS is important to prevent unnecessary tests and treatment also vaccination avoidance later.…”
Section: Discussionmentioning
confidence: 99%
“…1,[8][9][10] Vaccines associated with GCS are as following Haemophilus influenza type b (Hib); oral polio; diphtheria, pertussis, and tetanus (DPT); measles, mumps, and rubella (MMR); bacillus Calmette-Guerin (BCG); hepatitis B and A, and Japanese encephalitis. 1,5,9,11 It was reported in the literature that 21 out of 300 GCS cases were associated with vaccination. 9 There are two main hypotheses of GCS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations